Molecular detection of flavivirus in blood serum of rodents captured in Yucatán, Mexico - Torres-Castro, Marco (2017)
The aim of this investigation was to study the presence of flaviviruses in rodents from Yucatan, Mexico, by the Polymerase Chain Reaction (PCR) in the semi-nested variant. Ninety rodents were captured (87 Rattus rattus, two Heteromys gaumeri and one Mus musculus), and blood samples were collected. The resulting serum samples were grouped into 30 triads (pools). The semi-nested PCR yielded a positivity frequency of 33.3% (10/30).